Artificial Intelligence and the Human Brain: Exploring Effects on Cognitive Load, Memory, and Attention (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Artificial Intelligence (AI) has rapidly integrated into daily human activity, reshaping learning, working, and healthcare practices. While its potential to optimize efficiency is celebrated, there are rising concerns about its subtle yet significant effects on the human brain. This qualitative study explores how continuous reliance on AI influences cognitive load, memory retention, and attentional control. Data were gathered through semi-structured interviews with 40 participants, including students, educators, corporate professionals, health workers, and members of the general public. Four core themes emerged: (1) Cognitive Offloading and Dependency, (2) Memory Transformation, (3) Attention Fragmentation and Focus Shifts, and (4) Health and Wellbeing Concerns. Participants reported that while AI reduced task burden, it simultaneously created dependency, reshaped recall strategies, fragmented attention, and raised anxiety regarding overreliance. Interpretations suggest a paradox: AI lightens mental strain but erodes certain cognitive practices. The study highlights underexplored dimensions of how AI is reconfiguring mental functions, raising implications for education, workplace policies, and public health. Findings stress the importance of balancing AI use with active mental engagement to protect long-term cognitive health.